POTENSI PENCEMARAN DARI LIMBAH CAIR INDUSTRI PENGOLAHAN IKAN DI KECAMATAN MUNCAR, KABUPATEN BANYUWANGI - Setiyono, Setiyono; Yudo, Satmoko (Center for Environmental Technology, 2008)
Fish processing industries in Muncar-Banyuwangi have increased the welfare of the people there and made this area known as the major fish producer in Indonesia. More than 50% of its production has been exported to many countries and the rest has fulfilled domestic need. Although fish processing industry has developed quickly, its industrial pollution effect hasnÃ¢â‚¬â„¢t been handled well so that it polluted the surrounding envionment especially water surface. It happened because of using water for industrial need reached 17.883,2 m3 /day and almost all industries havenÃ¢â‚¬â„¢t provided a good wastewater installalion so that the environment couldnÃ¢â‚¬â„¢t handle and neutrilize the wastes. This paper explains condition of fish processing industries and potential load of the wastewater produced by them.Ã‚Â Keywords : Industri Pengolahan Ikan, Limbah Cair Industri, Pencemaran Lingkungan, Informasi.